You're Nicked: Investigating British Television Police Series, Ben Lamb (2020). Issue 3 (1st October 2020) - Addison, Michelle
You're Nicked: Investigating British Television Police Series, Ben Lamb (2020)Manchester: Manchester University Press, 232 pp., ISBN 978-1-52612-590-9, £80.00